Ebstein's anomaly in a newborn with prenatal diagnosis - Reynerio Cespedes Rojas; Yodalis Cedeño Ramírez; Osmara López Borrero (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2017)
Ebstein's anomaly encompasses a wide spectrum of abnormalities, characterized by different degrees of displacement and adhesion of the septal and posterior dysplastic valve of the tricuspid to the right ventricle cavity. As a consequence, tricuspid insufficiency, right ventricular failure and cyanosis appear. This study presents the case of a newborn from a cesarean delivery due to dystocia caused by loss of fetal well-being, with Apgar 8/9, weight 3650 grams and a prenatal diagnosis of Ebstein's disease followed by the provincial genetic department and the national group of genetics. It was born with distal and peribucal cyanosis that was improving as the hours went by and a GII / VI systolic heart murmur. The patient was assessed by cardio-pediatrics and a functional tricuspid insufficiency was determined, with pulmonary hypertension common of the age and a ductus in closing ways. In subsequent assessments evident clinical improvement was found with disappearance of the heart murmur. The patient progressed favorably with the disappearance of the distal cyanosis and was discharged asymptomatically with follow-ups by cardio-pediatrics.